2009
DOI: 10.1590/s1806-37132009000200002
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação semiquantitativa ecocardiográfica de dilatações vasculares intrapulmonares em candidatos a transplante hepático: correlação com avaliação de shunt e parâmetros funcionais pulmonares

Abstract: Objective: To correlate semiquantitative evaluation of intrapulmonary vascular dilatations (IPVD) with quantitative evaluation of shunt levels, as well as to describe clinical and pulmonary function findings in a sample of liver disease patients with IPVD. Methods: Patients presenting transthoracic echocardiography (TTE) positivity for IPVD underwent clinical evaluation, pulmonary function tests and pulmonary shunt quantification (scintigraphy with technetium-99m-labeled macroaggregated albumin and blood gas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
2
0
5
Order By: Relevance
“…It is worth mentioning that maximum microbubble density in the LA and LV was noted after cardiac cycle 7 in a quarter of the patients. In an earlier study that assessed bubble intensity in cirrhotic patients, Ferreira et al 25 also found a direct association between the degree of right-to-left shunting assessed by contrast echocardiography and nuclear scanning, though specific patterns of bubble appearance by cardiac cycle were not described.…”
Section: Discussionmentioning
confidence: 97%
“…It is worth mentioning that maximum microbubble density in the LA and LV was noted after cardiac cycle 7 in a quarter of the patients. In an earlier study that assessed bubble intensity in cirrhotic patients, Ferreira et al 25 also found a direct association between the degree of right-to-left shunting assessed by contrast echocardiography and nuclear scanning, though specific patterns of bubble appearance by cardiac cycle were not described.…”
Section: Discussionmentioning
confidence: 97%
“…[101102] The presence of numerous intrapulmonary shunts was first described by Hoffbauer et al , following which multiple imaging studies using various molecules confirmed these findings. [103105] Despite the relatively high prevalence of hypoxemia in cirrhotic patients, it is uncommon for these patients to die of respiratory failure. However, one study compared the median and 5 year survival in two groups with and without hepatopulmonary syndrome.…”
Section: The Pulmonary Circulationmentioning
confidence: 99%
“…É caracterizada por uma tríade, composta por: 1) oxigenação arterial anormal, definida pela European Respiratory Society Task Force, em 2004, como elevação do gradiente alvéolo-arterial de oxigênio (P(A-a)O2) > 15 mmHg, ou > 20 mmHg, na população com mais de 65 anos; 2) DVIP; e 3) doença hepática grave, HP, ou shunt porto-sistêmico congênito. A incidência da SHP, entre os pacientes que aguardam pelo LT, pode variar entre 4 e 47% (BORYCZKA et al, 2015;CARRION;MARTIN, 2021;CASTRO;KROWKA, 1996;CHEUNG et al, 2020;DELIK;ÜLGER, 2021;FERREIRA et al, 2009;KROWKA et al, 2016;LEJEALLE et al, 2019;RODRÍGUEZ-ROISIN;KROWKA, 2008;SOULAIDOPOULOS et al, 2018;VERCELINO et al, 2008;ZHANG;FALLON, 2012;ZHAO et al, 2018).…”
Section: Síndrome Hepatopulmonarunclassified
“…A DVIP é o principal achado patológico da SHP, caracterizada por marcante dilatação dos vasos pré-capilares e capilares pulmonares, que podem aumentar de 8-15 µm para 100-150 µm de diâmetro ao repouso, conforme representado na figura 2 (RODRÍGUEZ-ROISIN; KROWKA, 2008). A taxa de incidência de DIVP entre candidatos ao LT é variável de acordo com os diferentes autores na literatura, e pode oscilar entre 13 a 64% (ABRAMS et al, 1995;CARRION;MARTIN, 2021;CHEUNG et al, 2020;DUBROCK et al, 2018;FERREIRA et al, 2009;HOPKINS;WAGGONER;BARZILAI, 1992;KROWKA et al, 1990;PAVARINO et al, 2004;VEDRINNE et al, 1997). Entretanto, pouco se sabe sobre seu mecanismo fisiopatológico e impacto sobre os doentes, bem como sobre a progressão dessa condição com o decurso de hipoxemia e o desenvolvimento da SHP.…”
Section: Síndrome Hepatopulmonarunclassified
See 1 more Smart Citation